Cryptic genetic variation and adaptation to waterlogging in Caledonian Scots pine, Pinus sylvestris L. Issue 17 (2nd August 2018) - Donnelly, Kevin; Cavers, Stephen; Cottrell, Joan E.; Ennos, Richard A.
Abstract: Local adaptation occurs as the result of differential selection among populations. Observations made under common environmental conditions may reveal phenotypic differences between populations with an underlying genetic basis; however, exposure to a contrasting novel environment can trigger release of otherwise unobservable (cryptic) genetic variation. We conducted a waterlogging experiment on a common garden trial of Scots pine, Pinus sylvestris (L.), saplings originating from across a steep rainfall gradient in Scotland. A flood treatment was maintained for approximately 1 year; physiological responses were gauged periodically in terms of photochemical capacity as measured via chlorophyll fluorescence. During the treatment, flooded individuals experienced a reduction in photochemical capacity, F v /F m, this reduction being greater for material originating from drier, eastern sites. Phenotypic variance was increased under flooding, and this increase was notably smaller in saplings originating from western sites where precipitation is substantially greater and waterlogging is more common. We conclude that local adaptation has occurred with respect to waterlogging tolerance and that, under the flooding treatment, the greater increase in variability observed in populations originating from drier sites is likely to reflect a relative absence of past selection. In view of a changing climate, we note that comparatively maladapted populations may possess considerable adaptive potential, due to cryptic genetic variation, that should not be overlooked. Abstract : We conducted a waterlogging experiment on a common garden trial of Pinus sylvestris (L.) saplings originating from across a steep rainfall gradient in Scotland. Flooded individuals experienced a reduction in photochemical capacity, this reduction being greater for drier, eastern sites. Phenotypic variance was increased under flooding, and this increase was notably smaller for western sites where precipitation is substantially greater and waterlogging is more common. We conclude that local adaptation has occurred with respect to waterlogging tolerance and that the greater increase in variability observed in populations from drier sites is likely to reflect a relative absence of past selection.